Stromal cell heterogeneity in fibroblast growth factor-mediated stromal-epithelial cell cross-talk in premalignant prostate tumors - XIAOCHONG WU; CHENGLIU JIN; FEN WANG; CHUNDONG YU; MCKEEHAN, Wallace L (Cancer research (Chicago, Ill.), 2003)
Homeostasis of normal prostate and two-compartment nonmalignant prostate tumors is dependent on two-way communication between epithelial and stromal compartments. Independence of epithelial cells on controlling instructions from stroma is a hallmark of extremely malignant epithelial cell tumors. To better understand the evolution of stromal independence during malignant progression, we performed a clonal analysis of stromal cells derived from a well-defined model of two-way stromal-epithelial cell communication that loses response to stroma during prostate tumor progression. Directionally specific signaling from stroma to epithelium contributes to homeostasis between the two compartments. Stromal cells were characterized in respect to expression and activity of isotypes of the fibroblast growth factor (FGF) family of ligands and receptors in addition to morphology and cytoskeletal markers. One stromal subtype (DTS1) exhibited a fibroblast-like morphology and did not display smooth muscle cell (SMC) alpha-actin. The other (DTS2) exhibited SMC alpha-actin and an SMC-like morphology in vitro. Both subtypes expressed FGF7 and equally low levels of FGFR2IIIc mRNA, whereas fibroblast growth factor receptor (FGFR) 1 predominated in DTS1 cells. DTS1 cells also expressed FGF10 and no detectable FGFR3, whereas the absence of FGF10 and presence of FGFR3 distinguished DTS2 cells. Epithelial cell-derived FGF9 bound to FGFR and stimulated growth of specifically FGFR3-positive DTS2 cells, not the FGFR3-negative DTS1 cells. These results demonstrate stromal cell heterogeneity in signal reception of FGF from epithelium. This correlated with potential heterogeneity in the response back to epithelial cells. Epithelium-dependent control of a stromal cell phenotype within a tumor may be a determinant of whether tumors remain in nonmalignant homeostasis or progress to malignancy.